Pemanfaatan Lahan Kosong untuk Budidaya Hidroponik di Pekarangan Rumah dalam Meningkatkan Pendapatan Ekonomi Rumah Tangga di Kelurahan Sidomulyo Barat Kecamatan Tuah Madani Kota Pekanbaru - M. Imam Arifandy; Darusman Darusman (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The problem that often arises now is the increase in living costs while income remains constant. With empty land in the household that is not being utilized optimally, this should be an opportunity for housewives to help improve the household economy. One solution to utilize this empty land is through hydroponic plants. This hydroponic plant uses organic fertilizer so that the hydroponic plant is good for family consumption and distribution in supermarkets. By utilizing hydroponic plants, housewives can help improve the family's economy so that the family's needs can be fully met. In this research, the researcher conducted an interview with one of the housewives who had used her yard through hydroponic plants that she had developed herself since 2017. The aim of the research was to determine the economic improvement experienced by housewives after using the hydroponic system.